Common Fixed Point Results on Generalized Weak Compatible Mapping in Quasi-Partial b-Metric Space. (11th June 2021) - Gautam, Pragati; Sánchez Ruiz, Luis Manuel; Verma, Swapnil; Gupta, Gauri
Abstract : The focus of this paper is to acquaint with generalized condition (B) in a quasi-partial b-metric space and to establish coincidence and common fixed point theorems for weakly compatible pairs of mapping. Additionally, with the background of quasi-partial b-metric space, the outcomes obtained are exemplified to prove the existence and uniqueness of fixed point.